INFOGRAFIS VALIDASI KULIAH KERJA PRAKTEK DENGAN MEDIA AUDIO VISUAL - Sudaryono, Sudaryono; Desrianti, Dewi Immaniar; Lestari, Karunia Suci (Jurnal Ilmiah Sains dan Teknologi, 2018)
Media information has now been growing ranging from print media such as brochures, banners, banners and more. Even many who have used the audio visual media assupporting media information. For students who wish to take Kuliah Kerja Prkatek (KKP) there are still many who do not understand the validation stage of the KKP which is still shaped paper announcements, for it required info graphics about the stages of validation of the KKP in the form of audio media Visual. Audio visual media with someone will more easily understand the stages of validation of Kuliah Kerja Praktek. The animation technique is one of the media delivery information that is quite effective and appealing visuals help convey information are presented. There are some applications that are used in the manufacture of video infographics: CorelDrawis used to create vector of Character Building and Informant STMIK Raharja used for the background of the video infographics, in addition there is Adobe The AfterEffectis used as a display layout for the addition of the information to be communicated, and Adobe Premiere Pro is used to combine the entire video. The purpose of doing research is to help students to know in detail the stages of what should be done in the validation Work Practices and useful Lecture on behalf of the campus to convey how the process of validation of Kuliah Kerja Praktek to do before taking a Kuliah Kerja Praktek.